Traditional literature review: investigation of rhodamine b on street foods and sauce products in Indonesia - Agsari, Aulia Dwi; Guntarti, Any (Journal of Halal Science and Research, 2023)
Food is one of the most important basic human needs for growth and development. Generally, the types of food cater to tastes and look attractive. To make it look attractive and have good taste is usually added with food additives. The food products with the most coloring added are street foods, red sauces, and rainbow cakes that children love. Rhodamine B is a prohibited coloring agent and is not present in food because, for a long time, it will cause liver damage, tumors, and cancer. Therefore, an article review was conducted to determine the levels and methods that can be used to analyze Rhodamine B from several research journals that have been conducted. The literature review method uses the following keywords or terms and strategies: "analysis" AND "rhodamine B" AND "food" OR "chili sauce" for searches on PubMed and Science Direct, while Google Scholar uses the keywords "Analysis, Rhodamine B, makanan, Sauce." And the inclusion criteria used were: (1) research articles in the form of journals published in the last ten years (2010-2020), using both English and Indonesian, full text; (2) Articles that discuss the analysis of Rhodamine B in snack foods and sauces located in Indonesia; (3) proved to be positive for Rhodamine B. The results of the reviewed articles showed that there was still Rhodamine B content in snack foods and sauces used by traders. The analytical methods used for identification were TLC, color detection with wool yarn, Rhodamine B Rapit-test Kit, UV-Vis spectrophotometer, and Gravimetry. The highest levels of Rhodamine B were found at 194 ppm in tomato sauce. The review of articles that have been conducted shows that there is still Rhodamine B found in snack foods and sauces by traders, which can be harmful to health in the long and short term.